O regime de cooperação do Tribunal Penal Internacional: desafios da cooperação na detenção e entrega dos acusados - Joana de Andrade Pacheco (2020)
The successful trial of individuals by the International Criminal Court is highly dependent on State cooperation. Since it does not have its own police force, the ICC relies on the cooperation of States during all stages of the proceedings. The importance of the matter is recognized by the Rome Statute itself, which devotes an entire chapter to international cooperation and judicial assistance. Despite that, the lack of cooperation remains one of the main obstacles to the Court's operation, especially regarding the enforcement of arrest warrants. Therefore, this thesis aims to critically analyze the cooperation regime adopted by the ICC in order to try to identify the main challenges faced by it in the arrest and surrender of suspects. After assessing the relevant legislation, the considerations of the literature on the matter and the main cases of non-cooperation before the Court, the author sustains that the challenges faced by the ICC in securing the surrender of its suspects result not only from weaknesses in its legal regime, but also from problems in the application by this regime by the Court. Some of the criticisms to the cooperation regime established by the Rome Statute are the existence of exceptions to the obligation to cooperate, the lack of clarity of some provisions and the poor development of non-cooperation mechanisms. These problems are aggravated by the lack of uniformity in the interpretation and application of the provisions of Part IX, especially of arts. 87 (7) and 98 (1), which weaken the Court's authority and undermine its ability to compel non-cooperating states to fulfill their obligations. Regarding the strengthen of the cooperation regime, greater consistency in the application of non-cooperation mechanisms and greater support from the CS and the ASP is required. Assistance from other subjects and non-state actors, such as international organizations and civil society organizations, can also assist the ICC in securing the detention and surrender of its suspects.